Pembinaan Tari dan Musik Tradisional Kalimantan Tengah sebagai Pendidikan Karakter pada Siswa SMKN 1 Kuala Kapuas - Pahan, Berth Penny; Prasetya, Arly (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
The background of this research is how a teacher of Christian Religious Education and a teacher of Cultural Arts with different expertise backgrounds can conduct successful coaching. The objectives of this study are to find out and obtain an actual and factual picture of the work program, teacher creativity, and elements of character development in traditional dance and music in Central Kalimantan traditional dance and music extracurricular activities at SMKN 1 Kuala Kapuas, Kapuas Regency. Data collection techniques were carried out by observation, interviews, and documentation. Then the data analysis technique is done by reduction, exposure, and conclusion/verification. The results of the research are that the extracurricular activities of traditional dance and music development already have planning, funding, routine training schedule, training facilities, completeness of dancers and musicians, performance targets and competitions at the district, provincial, and national levels. The creativity carried out by the coaching teacher is to make an annual work program, clear goals and objectives for a year. The elements found in traditional dance and music in Central Kalimantan are elements of history, regional culture, and music. Latar belakang penelitian ini bagaimana seorang guru Pendidikan Agama Kristen dan seorang guru Seni Budaya yang berbeda latar belakang keahliannya dapat melakukan pembinaan yang berhasil. Adapun tujuan penelitian ini adalah untuk mengetahui dan memperoleh gambaran secara aktual dan faktual mengenai program kerja, kreativitas guru, dan unsur-unsur pengembangan karakter dalam seni tari dan musik tradisional pada kegiatan ekstrakurikuler tari dan musik tradisional Kalimantan Tengah di SMKN 1 Kuala Kapuas, Kabupaten Kapuas. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Kemudian untuk teknik analisa data dilakukan dengan reduksi, paparan, dan kesimpulan/verifikasi. Hasil penelitian bahwa kegiatan ekstrakurikuler pembinaan tari dan musik tradisional sudah memiliki perencanaan, pendanaan, jadwal latihan rutin, fasilitas latihan, kelengkapan penari dan pemusik, target penampilan dan lomba tingkat kabupaten, provinsi, dan nasional. Kreativitas yang dilakukan oleh guru pembina adalah membuat program kerja tahunan, tujuan dan sasaran yang jelas selama setahun. Unsur yang ditemukan dalam seni tari dan musik tradisional Kalimantan Tengah adalah unsur sejarah, budaya daerah, dan musik.